The Fantastic Life of Walter Murray Gibson Hawaii's Minister of Everything - Adler, Jacob (University of Hawai'i Press, 1986)
Walter Murray Gibson is one of the most enigmatic personalities in nineteenth-century Hawaiian history. Michener and Day saw him as an engaging rogue and included him in their Rascals in Paradise along with buccaneer Bully Hayes and Captain Bligh. Gavan Daws portrayed him in A Dream of Islands as a romantic and compassionate man who rashly challenged the ascendant planter-missionary party at a decisive period in Hawaii's political history. Imbued since youth with grandiose ideals and soaring flights of fantasy, Gibson pursued throughout his life the dream of an island utopia flourishing under his leadership The East Indies beckoned first, and there on the island of Sumatra Gibson sought his fortune, finding instead a Dutch prison cell on Java. Recast as a Mormon, the High Priest of Melchizedek and chosen emissary of Brigham Young, Gibson gathered his flock about him on the island of Lanai, and was judged by the church to deserve excommunication. He finally realized his dream as Kipikona, Kalakaua's "Minister of Everything," the most skilled politician of his day, only to be driven from office and publicly taunted with a hangman's noose. Authors Adler and Kamins bring historical reality to this turbulent and controversial life story. Carefully researched and engagingly written, The Fantastic Life of Walter Murray Gibson shows the many sides of this man of myriad talents--adventurer, New York businessman, Washington lobbyist, scholar, newspaper editor, orator, rancher, consummate legislative leader, "Minister of Everything," and, always, a dreamer who dared to reach for the sun.